PERAN KOMUNIKASI DALAM KELUARGA BEKERJA (STUDI KASUS PADA ANAK PASANGAN BEKERJA) - Triyandra, Annisa Citra; Arif, Ernita; Asmawi, Asmawi (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2020)
The concept of Work-Family is now no stranger to the general public. Work- family is a concept of family who must fulfill the roles that must be carried out as a family and work activities. When parents are preoccupied with they work, they also need to take time to accompany their children to listen to complaints or stories of their children's daily life. In this study, researchers want to know how the role of communication in working families, how the response of a child who has working parents, and see what conflicts occur in the working family. This research uses descriptive qualitative research methods. The results of this study indicate that the communication that exists between the child and both parents who work runs smoothly. Parents always try to take the time to talk about their daily activities. However, it does not always run smoothly, sometimes a strain based conflict also arises, where fathers and mothers are too focused on their work. Child feels the reduced attention from the parents. In this case the role of communication is needed to discuss each other's desires (children and parents). In addition, the role of communication is needed to show the concern and affection among each family member.